Ethical governance of artificial intelligence in the public sector - Saban, Liza Ireni; Sherman, Maya (Routledge, 2022)
This book argues that ethical evaluation of AI should be an integral part of public service ethics and that an effective normative framework is needed to provide ethical principles and evaluation for decision-making in the public sphere, at both local and international levels.